2016
DOI: 10.1093/occmed/kqw054
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk among workers of a secondary aluminium smelter: Table 1.

Abstract: Results of this study suggest that work at secondary aluminium smelters is associated with bladder cancer risk. Identification of occupational carcinogens in this industry is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
2
3
0
2
Order By: Relevance
“…This analysis of >121 700 person-years of follow-up among 4507 male employees in prebake aluminium smelters found no differences in the rates of overall mortality and, in particular, mortality from overall cancer and non-malignant respiratory disease, compared with the Australian population. Among the workers likely to have been most exposed (production and maintenance workers), there was a lower risk of overall death and overall cancer deaths in the 20 years after commencing work, consistent with results published previously7 and those from other studies18 19 among smelter workers and likely attributable to the healthy worker effect. An excess risk of lung (SMR 1.4, 95% CI 1.0 to 1.8), prostate (SMR 1.9, 95% CI 1.3 to 2.7) and liver cancer (SMR 2.0, 95% CI 1.1 to 3.4) was seen among production workers in whom an increased SIR for overall respiratory cancers (lung cancers) was also found.…”
Section: Discussionsupporting
confidence: 89%
“…This analysis of >121 700 person-years of follow-up among 4507 male employees in prebake aluminium smelters found no differences in the rates of overall mortality and, in particular, mortality from overall cancer and non-malignant respiratory disease, compared with the Australian population. Among the workers likely to have been most exposed (production and maintenance workers), there was a lower risk of overall death and overall cancer deaths in the 20 years after commencing work, consistent with results published previously7 and those from other studies18 19 among smelter workers and likely attributable to the healthy worker effect. An excess risk of lung (SMR 1.4, 95% CI 1.0 to 1.8), prostate (SMR 1.9, 95% CI 1.3 to 2.7) and liver cancer (SMR 2.0, 95% CI 1.1 to 3.4) was seen among production workers in whom an increased SIR for overall respiratory cancers (lung cancers) was also found.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with that of previous studies 36 . An elevated risk of bladder cancer has often been found in metalworking occupations, but most have not addressed MWFs exposure using quantitative measurements, therefore it's not clear which agents in MWFs are attributable to the bladder cancer risk 36‐39 . On the basis of quantitative measurements, only one cohort study has been conducted and has reported an increased risk of bladder cancer in association with MWFs 40 …”
Section: Discussionsupporting
confidence: 86%
“…36 An elevated risk of bladder cancer has often been found in metalworking occupations, but most have not addressed MWFs exposure using quantitative measurements, therefore it's not clear which agents in MWFs are attributable to the bladder cancer risk. [36][37][38][39] On the basis of quantitative measurements, only one cohort study has been conducted and has reported an increased risk of bladder cancer in association with MWFs. 40 Occupational exposure to aromatic amines, that is, 4-aminobiphenyl, 2-naphthylamine, benzidine and its metabolites have been classified as carcinogenic to humans and are strongly and consistently associated with bladder cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Al has been shown to be particularly dangerous for the functioning of the central nervous system, causing cognitive and neurodegenerative disorders. Many studies have shown that exposure to Al can cause neuropsychiatric and neurological symptoms, as well as diseases such as Alzheimer’s disease, risk of cognitive impairment, dementia, allergic conditions, inflammatory skin lesions, and a higher risk of developing lung cancer or bladder cancer [ 64 , 65 , 66 , 67 ]. Yoshimasu et al found higher concentrations of Al in the brain of victims of amyotrophic lateral sclerosis (ALS) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%